Synthesis, crystal structure and in vitro DNA binding studies of combretastatin A-4 analogue - Rizvi, Masood Ahmad; Dangat, Yuvraj B.; Yaseen, Zahid; Gupta, Vivek; Khan, Khaliquz Zaman (Croatica Chemica Acta, 2015)
Synthesis of a novel Combretastatin A-4 analogue using Schiff's reaction of benzil and 4-aminoantipyrine has been achieved under solvent free conditions. The structure of compound was examined spectroscopically and confirmed from single crystal diffraction studies. The synthesized Combretastatin A-4 analogue was investigated for its DNA binding ability as the plausible mechanism for its antitumor activity. The binding propensity of the synthesized compound with calf-thymus (CT) DNA was monitored with absorption and emission spectrophotometric titrations. The calculations predict a binding constant of 7.24 x 10(4) for the complex of the synthesized compound with CT DNA which is comparable in magnitude to that of DNA binding of bactericidal drug enoxacin and typical intercalation indicator ethidium bromide (EB). Competitive binding studies of the synthesized compound with EB using fluorescence titration reveal that it displaces the DNA-bound EB and binds in intercalative mode which was further supported by circular dichroism (CD) spectroscopy. The probable site and binding energy of the compound with DNA was further theoretically investigated by molecular docking studies. The significant DNA binding ability of the synthesized Combretastatin A4 analogue as revealed from this study could be related to the anticancer activity of the Combretastatin A4.
Keywords: benzil; bio-physical; combretastatin A-4; crystal structure; DNA binding; ethidium bromide; fluorescence; phenazones

Tetranuclear cubane Cu4O4 complexes as prospective anticancer agents: Design, synthesis, structural elucidation, magnetism, computational and cytotoxicity studies - Usman, Mohammad; Arjmand, Farukh; Khan, Rais Ahmad; Alsalme, Ali; Ahmad, Musheer; Sen Bishwas, Mousumi; Tabassum, Sartaj (Inorganic Chimica Acta, 2018)
Two new homometallic Cu4O4 cubane clusters 1 and 2 have been synthesized by self-assembly of copper (II) acetate and ligand, 2-[(2-Hydroxy-3-methoxy-benzylidene)-amino]-2-hydroxymethyl-propane-1, 3-diol (H4L) and characterized thoroughly by various spectroscopic techniques and single crystal X-ray diffraction analysis. Temperature- dependent magnetic susceptibility measurements have been performed to elucidate the antiferromagnetic and ferromagnetic nature in Cu4O4 clusters 1 and 2, respectively. In vitro DNA binding studies of cubane clusters were carried out by employing optical spectroscopic techniques. Gel electrophoretic mobility assay performed to examine the nuclease activity of the complexes 1 and 2 with pBR322 DNA, and results revealed oxidative DNA cleavage via reactive oxygen species (ROS) species viz., O-2(.-), O-1(2), etc. In vitro cell proliferation via MTT assay was studied to calculate the cytotoxicity of complexes 1 and 2. The IC50 evaluated were similar to 20 mu M in MCF-7 (Breast) and similar to 30-35 mu M in HepG2 (Liver) cancer cell lines. Additionally, in the presence of 1 and 2, ROS and TBARS (Thiobarbituric acid reactive substance) levels amplified significantly, coupled with GSH (glutathione) levels in cancer lines. Hence, the results exhibited the major role of ROS in apoptosis induced by 1 and 2 clusters and validate their prospective to be efficient anticancer drug entities. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Cu4O4 cubane complexes; Cytotoxicity; DFT; DNA binding; Magnetism; Nuclease activity